Dimensionamento prático à força cortante de seções de concreto armado - Cunha, Mario Terra (1981)
Practical procedures for shear design of reinforced concrete members, with the aid of a programmable calculator, are hereby presented. These procedures result from simplifications on a mechanical model of a cracked reinforced concrete plate, aiming its application to the usual design of reinforced concrete. With the simplified model, shear stresses, corresponding to the tangential components of the compressive stresses on the concrete struts, may be determined through an equivalent concrete section. The equivalent section method could be applied torectangular cross-section linear members with a vertical symetry axis. The application of this method could be extended to members with other cross-sectional shapes, provided that no sharp variation occurs in their width and the symmetry in relation to the z axis is maintained, as it occurs with the circular cross-section members. ln order to permit the use of this method in programmable calculators, a computer program was developed in FORTRAN IV language, generating tables which allow the determination of the axial deformation and the curvature of circular and rectangular section.